Analisis Puisi “Puisi Untuk Ibu” Karya H. Muhamad Ichsan Dengan Menggunakan Pendekatan Struktural - Tanti Tanti; Dinda Amanda (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
In literary works, for example, literary works in the form of poetry, there must be a form of appreciation and study of literary works that have been created. This study discusses the study of poetry in poetry literature entitled